20 Years of Persistent Identifiers – Which Systems are Here to Stay?. (22nd March 2017) - Klump, Jens; Huber, Robert
Web-based persistent identifiers have been around for more than 20 years, a period long enough for us to start observing patterns of success and failure. Persistent identifiers were invented to address challenges arising from the distributed and disorganised nature of the internet, which often resulted in URLs to internet endpoints becoming invalid. Over the years several different persistent identifier systems have been applied to the identification of research data, not all with the same level of success in terms of uptake and sustainability. We investigate the uptake of persistent identifier systems and discuss the factors that might determine the stability and longevity of these systems. Persistent identifiers have become essential elements of global research data infrastructures. Understanding the factors that influence the stability and longevity of persistent identifier systems will help us guide the future development of this important element of research data infrastructures and will make it easier to adapt to future technological and organisational changes.